"Perrotta Affective Dependence Questionnaire (PAD-Q)": Psychodiagnostic evidence and clinical profiles - Giulio Perrotta (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2021)
Purpose: Starting from the concept of "affective dependence" and its international nosographic framework, the Perrotta Affective Dependence Questionnaire (PAD-Q) aims to study the phenomenon of "affective dependence", defining it as a maladaptive model of the affective-sentimental relationship of a couple, which involves the establishment or persistence of a clinically significant bond, lasting at least six months and characterized by a functional impairment of the relational area, the emotional area and the somatic area. Affective addiction, not being a well-identified psychopathological label in the international nosographic framework, except in the general framework of behavioral addictions, in this context is identified as a maladaptive behavioral model that describes a series of personality traits afferent to several nosographically recognized psychopathological disorders [1]. Methods: Administration of the PICI-1 and PAD-Q. Clinical Interview.  Results: The present research work has demonstrated the reliability, efficiency and effectiveness of the PAD-Q, in relation to the objectives and the PICI-1. In particular, it facilitated a better diagnostic framing of current affective behavioral addiction, thus allowing to focus attention on the dysfunctional traits of patients and on the correct psychodiagnostic framing and their eventual clinical treatment.  Conclusions: The results of the PICI-1 on the selected population sample is perfectly compatible with the results of the PAD-Q, underlining also the trend according to which the higher the age of the population sample the higher the diagnosis of cluster B disorders, up to the highest psychotic percentage in the most mature age group. The same trend is visible in the PAD-Q data, which confirms the greater presence of dysfunctional traits in cluster B disorders.